2016
DOI: 10.1111/ijpo.12183
|View full text |Cite
|
Sign up to set email alerts
|

Association between plasminogen activator inhibitor‐1 and severity of liver injury and cardiovascular risk in children with non‐alcoholic fatty liver disease

Abstract: SummaryBackground: Plasminogen activator inhibitor-1 (PAI-1) is the primary inhibitor of the endogenous fibrinolytic system and is known to be increased in obesity, insulin resistance and non-alcoholic fatty liver disease (NAFLD). We previously demonstrated that PAI-1 levels were closely related to the amount of hepatic steatosis in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…In this regard, plasminogen activator inhibitor-1 (PAI-1) has been suggested as an early marker of metabolic health in obese children, 40 strongly related to lipids and insulin resistance. 41 It is therefore evident that obese children have a higher prevalence of CVD risk factors compared with normal weight peers. The clustering of risk factors in obese children is detrimental to their health as these risk factors accumulate as the children grow into adulthood.…”
Section: Insulin Resistance and Diabetesmentioning
confidence: 99%
“…In this regard, plasminogen activator inhibitor-1 (PAI-1) has been suggested as an early marker of metabolic health in obese children, 40 strongly related to lipids and insulin resistance. 41 It is therefore evident that obese children have a higher prevalence of CVD risk factors compared with normal weight peers. The clustering of risk factors in obese children is detrimental to their health as these risk factors accumulate as the children grow into adulthood.…”
Section: Insulin Resistance and Diabetesmentioning
confidence: 99%
“…Plasminogen activator inhibitor-1 (PAI-1) is an acute-phase protein which increases in states of insulin resistance, inflammation, and injury [ 8 ] and is elevated in both adults and children with hepatic steatosis [ 9 11 ]. Furthermore, PAI-1 correlates with fibrosis stage [ 12 , 13 ]. The renin-angiotensin system (RAS) has been suggested to be involved in liver damage pathways and might play a critical role in the pathogenesis of NAFLD [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Serpine1 named also PAI-1 plays a key role as inhibitor of fibrinolysis and important roles in inflammation and wound healing. Over-expression of PAI-1 has been related to diabetes and metabolic syndrome features, while hepatic over-expression of PAI-1 has been coassociated with NAFLD severity/type and insulin resistance (Jin et al 2018), which implies the potential targeting of hepatic PAI-1 as a possible marker for diabetic/metabolic syndrome progress. Interestingly, in this context, a study of human hepatic gene expression in health versus diabetes has reported down-regulation of plasminogen in diabetic subjects (Takamura et al 2004).…”
Section: De Genes Of the Inflammatory Systemmentioning
confidence: 99%